Topical immunotherapy for Pseudomonas keratitis : use of antilipopolyssacharide plasma - Rauch, Andrew Johan (Rhodes University, Faculty of Pharmacy, Pharmacy, 1984)
Pseudomonas aeruginosa is an opportunistic pathogen capable of infecting the human cornea. Such infections are difficult to treat, and are often fulminative, in that the infected eye is lost, or severely scarred. The use of alternative therapeutic agents has been necessitated by the frequent failure of conventional antibiotic therapy. Equine hyperimmune antilipopolysaccharide plasma (Anti-LPS) was obtained by the plasmapheresis of suitably immunized horses. The plasma contained 1,O- 1 ,5g/ml of LPS-precipitible IgG antibodies. Topical administration of Anti-LPS as a lavage was shown to be effective against Pseudomonas keratitis in rabbits and guinea pigs. Subsequent use of topical corticosteroids was found to further reduce corneal pathology. The improvement noted in these experimental infections involved all three parameters measured, area of keratitis, depth of lesion, and degree of vascularization. In vitro , Anti-LPS was shown to be rapidly bactericidal for Gram negative bacteria. The plasma can therefore be said to have a dual mechanism of action: antitoxic, and antibacterial. Ocular administration of Anti-LPS, by both the topical and subconjunctival routes, was well tolerated by both rabbits and baboons. In conclusion, Anti-LPS is a potentially useful immunotherapeutic agent with many applications in both veteriary and human medicine, particularly in the treatment of surface infections involving antibiotic-resistant Gram negative bacteria,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Pseudomonas infections; Immunotherapy